Peer mentoring for smoking cessation in public housing: A mixed-methods study - Apata, Jummai; Goldman, Erica; Taraji, Hamideh; Samagbeyi, Oluwatobi; Assari, Shervin; Sheikhattari, Payam (Frontiers in Public Health, 2023)
Tobacco use disproportionately affects low-income African American communities. The recent public housing smoke-free policy has increased the demand for effective smoking cessation services and programs in such settings. This pilot study examined the potential impact of a peer-mentoring smoking cessation program in a public housing unit. Peer motivators were identified and trained from a community based smoking cessation initiative who then trained three residents of the public housing complex as peer mentors. Each peer mentor recruited up to ten smokers and provided them individual support for 12 weeks. A follow-up investigation was conducted three months after the completion of the 12-week intervention. At baseline and follow-up, the participants' smoking status was verified using exhaled carbon monoxide (eCO) monitoring. Qualitative information was collected via focus group discussions with peer mentors and participants. From 65 public housing residents who were surveyed, 44 of them were current smokers, out of which 30 were enrolled into the program. Overall mean eCO levels dropped from 26 ppm (SD 19.0) at baseline to 12 (SD 6.0) at follow-up (P <0.01). Participants who were enrolled in our program were more likely to have non-smoking eCO levels (<7ppm) at follow-up (23.3% compared to 14.3%) compared to those who did not enroll. Using peers as mentors may be helpful in providing services for hard-to-reach populations.